Pemberdayaan Bank Sampah Gemi Nastiti untuk Meningkatkan Kesejahteraan dan Kualitas Lingkungan di Desa Makamhaji Kecamatan Kartosuro Kabupaten Sukoharjo: Empowerment of Gemi Nastiti Waste Bank to Improve Welfare and Environmental Quality in Makamhaji Village, Kartosuro District, Sukoharjo Regency - Wiwit Rahayu; Darsono Darsono; Sri Marwanti; Minar Ferichani; Umi Barokah; Ernoiz Antriyandarti; Susi Wuri Ani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
In Sukoharjo Regency, more than 140 tons/day of waste goes to the TPA. One of the efforts to solve the waste problem is by establishing a waste bank, one of which is the "Gemi Nastiti" waste bank located in RT 01 RW XI Gobayan, Makamhaji, Kartosuro. As a waste bank that was just formed on September 26, 2021, the problems faced by the waste bank "Gemi Nastiti" in achieving its goals include management problems, inadequate infrastructure, and the skills of the management and members in utilizing waste into goods of economic value. In order to help solve these problems, this service activity is carried out to empower the "Gemi Nastiti" waste bank through waste bank management training, introduction of infrastructure facilities, and training on the use of waste into goods of economic value. The service activities that have been carried out have made the management and members of the Gemi Nastiti waste bank have knowledge and skills related to waste bank management and making handicrafts from plastic waste. In addition, the Gemi Nastiti waste bank has infrastructure to improve the performance of the waste bank in the form of digital scales, closed plastic buckets for each member and handicraft making equipment from plastic waste. In the end, this activity is able to empower the Gemi Nastiti waste bank so that it can improve the welfare and quality of the environment.